Syntax Errors in The Qur'an - Mohd Rafi, Fakhrur Razi; Nurbayan, Yayan; Al Farisi, M. Zaka (ADDIN, 2019)
This research is motivated by the thought of an orientalist–‘Abdallah ‘Abd al-Fadi–which states that the Qur’an has no perfection. He poured his thoughts into a book Is The Qur’an Infallible? In his book, he states that the Qur’an contains 22 Arabic syntax errors. His thoughts effected in many Muslims doubtful towards the authenticity of the Qur’an. In addition, non-Muslims also increasingly undermine the authenticity of it. Considering that this issue is a matter that must be addressed, the researcher will research further in this case. The purpose of this study is to refute the thoughts of ‘Abdallah ‘Abd al-Fadi and to maintain the purity, image, and authenticity of the Qur’an. The research method used in this research is descriptive analysis with the qualitative approach. The finding of this research indicates that ‘Abdallah ‘Abd al-Fadi’s thoughts on Qur’anic verses are wrong and this is due to his lack of understanding of Arabic theories especially the theories of Arabic syntax.